Quantification of dihydroartemisinin, artesunate and artemisinin in human blood: overcoming the technical challenge of protecting the peroxide bridge. (July 2011) - Lindegardh, Niklas; Hanpithakpong, Warunee; Kamanikom, Benjamas; Pattayaso, Janhom; Singhasivanon, Pratap; White, Nicholas J; Day, Nicholas PJ
Background: Quantification of artemisinin (ARN) and its derivatives in whole blood has hitherto been thought impossible.Results: A LC––MS/MS method for the analysis of artesunate (ARS), its metabolite dihydroartemisinin (DHA) and artemisinin in human whole blood has been developed and successfully validated. The method includes stabilization of the blood matrix at the time of collection and at the time of analysis. Addition of potassium dichromate to the blood samples deactivated the Fe 2+ core in hemoglobin, while deferoxamine chelated Fe 3+ and prevented back conversion into Fe 2+ . A pilot study showed that the blood:plasma ratio for ARS and DHA is approximately 0.75, indicating a significantly lower uptake in red blood cells than had previously been estimated using radiolabeled drug methodology.Conclusions: The developed LC––MS/MS assay is the first method available for quantification of ARN and its derivatives in blood and opens up new possibilities of studying these drugs inside infected red blood cells.